Connecting Computational Thinking (CT) Concept with the Game-Based Learning (GBL) Elements - Emram Yunus (International Association of Online Engineering (IAOE), 2021)
This study aims to identify the game-based learning component (GBL) and the concept of computational thinking (CT) that can be integrated together in a design model. GBL and CT concept components are obtained through analysis of previous research and specialist consultancy. The method of analytical analysis is based on the Kitchenham method, (2004) which consists of 3 phases i.e. planning, implementation and documentation. This analysis started on March to May 2020 and involved 398 articles related to GBL and CT.  However, there are only 15 articles on the development element of the GBL application and 8 articles related to the CT concept were used. During an expert consultancy, 15 specialists was involved in various backgrounds and experience in GBL and CT. The result shows that there are 6 main elements and 21 sub-elements of GBL. 6 main elements consist of rules, objectives, feedback, interactions, challenges and narrative. Meanwhile, the sub-element consists of the operating rules, basic rules, explicit rules and behaviours, measures, goals, gamification purposes, marks, rewards, badges/awards, player charts, characters, consequences, constraints, levels of games, fun, competition, control, space, engagement and curiosity that have been matched with their main elements. The main element and sub-element of the GBL is called GBL component. Each of these GBL components is integrated with 7 concepts of CT i.e. decomposition, algorithm, abstraction, logical reasoning, assessment, evaluation, pattern recognition and automation.